Comparative immunogenicity and neutralizing antibody responses post heterologous vaccination with CoronaVac (Sinovac) and Vaxzevria (AstraZeneca) in HIV-infected patients with varying CD4+ T lymphocyte counts - Sorawit Chittrakarn; Pisud Siripaitoon; Sarunyou Chusri; Siripen Kanchanasuwan; Boonsri Charoenmak; Thanaporn Hortiwakul; Phaiwon Kantikit; Narongdet Kositpantawong (Taylor & Francis Group, 2024)
ABSTRACTThe immune response to heterologous coronavirus disease (COVID-19) vaccination in people living with HIV (PLWH) is still unclear. Herein, our prospective cohort study aimed to compare the immune response of heterologous vaccination with CoronaVac (Sinovac) and Vaxzevria (AstraZeneca) between PLWH having CD4 counts ≤ 200 cells/µL (low CD4+) and > 200 cells/µL (high CD4+). Anti-receptor-binding domain (RBD) immunoglobulin G (IgG) levels and the percentage inhibition of neutralizing antibodies (nAbs) were analyzed at 2 and 12 weeks after immunization. Participants in the low and high CD4+ groups had mean CD4+ counts of 139 and 575 cell/µL, respectively. Two and 12 weeks after immunization, in the low CD4 group, the median anti-RBD-IgG levels were 159 IU/mL and 143 IU/mL, respectively, whereas the nAb level was 71% and decreased to 47.2%, respectively. Contrarily, the median anti-RBD-IgG levels in the high CD4+ group were 273 IU/mL and 294 IU/mL, respectively, whereas the nAb levels were 89.3% and relatively stable at 81.6%. However, although immune responses between the two study groups were not significantly different, a decline in nAb levels was observed at 12 weeks in the low CD4+ group. Therefore, a COVID-19 booster vaccine dose is suggested for immunoprotection.